2015
DOI: 10.1186/s12976-015-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

A Boolean network model of human gonadal sex determination

Abstract: BackgroundGonadal sex determination (GSD) in humans is a complex biological process that takes place in early stages of embryonic development when the bipotential gonadal primordium (BGP) differentiates towards testes or ovaries. This decision is directed by one of two distinct pathways embedded in a GSD network activated in a population of coelomic epithelial cells, the Sertoli progenitor cells (SPC) and the granulosa progenitor cells (GPC). In males, the pathway is activated when the Sex-Determining Region Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…A benefit of using these Boolean models is that they could serve as the ground-truth regulatory networks to evaluate the performance of proposed GRNs. We collected four Boolean models for Mammalian Cortical Area Development (mCAD) [28], Ventral Spinal Cord Development (VSC) [29], Hematopoietic Stem Cell Differentiation (HSC) [30], and Gonadal Sex Determination (GSD) [31]. Figure 4(a) displays these networks.…”
Section: Datasets From Curated Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A benefit of using these Boolean models is that they could serve as the ground-truth regulatory networks to evaluate the performance of proposed GRNs. We collected four Boolean models for Mammalian Cortical Area Development (mCAD) [28], Ventral Spinal Cord Development (VSC) [29], Hematopoietic Stem Cell Differentiation (HSC) [30], and Gonadal Sex Determination (GSD) [31]. Figure 4(a) displays these networks.…”
Section: Datasets From Curated Modelsmentioning
confidence: 99%
“…Gonadal Sex Determination. Rios et al 2015 modeled the gonadal differentiation circuit that regulates the maturation of the Bipotential Gonadal Primordium (BGP) into either male (testes) or female (ovary) gonads [31]. The model consists of 18 genes and a node representing the Urogenital Ridge (UGR), which serves as the input to the model.…”
Section: Hematopoietic Stem Cell Differentiationmentioning
confidence: 99%
“…In vitro and animal studies observed an impaired gene expression of steroidogenic enzymes and hormones associated with male reproductive health after the exposure to phthalates [ 245 , 246 ]. Besides, the phthalates modification of gene expression can also influence the onset of cancer.…”
Section: Intracellular Signaling Mechanisms Of Phthalates’ Action mentioning
confidence: 99%
“…This is truly surprising as it does not require any kinetic constants, as was first noted by Albert and Othmer (2003b). Today, examples of such models range from cell cycle control networks, developmental circuits, to apoptosis and cancer networks, among others (Mendoza et al 1999;Thieffry 2001,2003;Albert and Othmer 2003;Espinosa-Soto 2004;Li et al 2004;Zhang 2008;Bornholdt 2008a, 2013;Faure and Thieffry 2009;Krumsiek et al 2011;Lovrics et al 2014;Zañudo and Albert 2015;Ríos et al 2015;Zhou et al 2016b;Arias Del Angel et al 2018;Yachie-Kinoshita et al 2018;Zañudo et al 2018). Even a tinker toy set for simulating small genetic networks from biology with hardware Boolean networks is available today (Bornholdt and Kopperschmidt 2015).…”
Section: Introductionmentioning
confidence: 99%